Penyusunan Ensiklopedia Makanan Khas Sumatra Barat - Maharani, Nuryusro; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractIn this writing discussed about making a food encyclopedia typical of West Sumatra. The purpose of writing this paper aims to describe the making of an encyclopedia of typical food in West Sumatra. The research method used in this study is descriptive method with data collection techniques through interviews. Data collection through interviews was conducted with the communities in each region in West Sumatra. Based on the data analysis, it can be concluded that the stages in the making of the encyclopedia of West Sumatra typical foods are as follows: 1) information tracing to every region in West Sumatra; 2) Collection of food data typical of West Sumatra is collected based on the results of the search for information from information sources, namely typical restaurant outlets in each region in West Sumatra; 3) the editing or checking process is carried out by completing the lack of writing the wrong word; 4) create a printed encyclopedia for West Sumatra food.Â Keywords: food, West Sumatra, and encyclopedia